Bayesian model selection for complex dynamic systems - Mark, Christoph; Metzner, Claus; Lautscham, Lena; Strissel, Pamela; Strick, Reiner; Fabry, Ben (Nature Communications, 2018)
Time series generated by complex systems like financial markets and the earth's atmosphere often represent superstatistical random walks: on short time scales, the data follow a simple low-level model, but the model parameters are not constant and can fluctuate on longer time scales according to a high-level model. While the low-level model is often dictated by the type of the data, the high-level model, which describes how the parameters change, is unknown in most cases. Here we present a computationally efficient method to infer the time course of the parameter variations from time-series with short-range correlations. Importantly, this method evaluates the model evidence to objectively select between competing high-level models. We apply this method to detect anomalous price movements in financial markets, characterize cancer cell invasiveness, identify historical policies relevant for working safety in coal mines, and compare different climate change scenarios to forecast global warming.
EVALuna2:210064

Biomembrane-mimicking lipid bilayer system as a mechanically tunable cell substrate - Lautscham, Lena; Lin, Corey Y.; Auernheimer, Vera; Naumann, Christoph A.; Goldmann, Wolfgang; Fabry, Ben (Biomaterials, 2014)

CAS directly interacts with vinculin to control mechanosensing and focal adhesion dynamics - Janoštiak, Radoslav; Brabek, Jan; Auernheimer, Vera; Tatárová, Zuzana; Lautscham, Lena; Dey, Tuli; Gemperle, Jakub; Merkel, Rudolf; Goldmann, Wolfgang; Fabry, Ben; Rosel, Daniel (Cellular and Molecular Life Sciences, 2014)

Identification of DAPK as a scaffold protein for the LIMK/cofilin complex in TNF-induced apoptosis - Ivanovska, Jelena; Tregubova, Alexandra; Mahadevan, Vijayalakshmi; Chakilam, Saritha; Gandesiri, Muktheshwar; Benderska, Natalya; Ettle, Benjamin; Hartmann, Arndt; Söder, Stephan; Ziesche, Elisabeth; Fischer, Thomas; Lautscham, Lena; et al. (International Journal of Biochemistry and Cell Biology, 2013)
The role of cytoskeleton-associated proteins during TNF-induced apoptosis is not fully understood. A potential candidate kinase that might connect TNF signalling to actin reorganization is the death-associated protein kinase (DAPK). To identify new DAPK interaction partners in TNF-induced apoptosis, we performed a peptide array screen. We show that TNF-treatment enhanced the phosphorylation of LIMK at threonine508 and its downstream target cofilin at serine3 (p-cofilin(Ser3)). Modulation of DAPK activity and expression by DAPK inhibitor treatment, siRNA knockdown, and overexpression affected the phosphorylation of both proteins. We propose a 3D structural model where DAPK functions as a scaffold for the LIMK/cofilin complex and triggers a closer interaction of both proteins under TNF stimulation. Upon TNF a striking redistribution of LIMK, DAPK, and cofilin to the perinuclear compartment was observed. The pro-apoptotic DAPK/LIMK/cofilin multiprotein complex was abrogated in detached cells, indicating that its signaling was no longer needed if cells committed to apoptosis. P-cofilin(Ser3) was strongly accumulated in cells with condensed chromatin, pronounced membrane blebs and Annexin V up-regulation. From studying different cofilin(Ser3) mutants we suggest that p-cofilin(Ser3) is an indicator of TNF-induced apoptosis. Collectively, our findings identify a novel molecular cytoskeleton-associated mechanism in TNF-induced DAPK-dependent apoptosis.

Inhibition of Rho kinases increases directional motility of microvascular endothelial cells - Breyer, Johannes; Samarin, Jana; Rehm, Margot; Lautscham, Lena; Fabry, Ben; Goppelt-Strübe, Margarete (Biochemical Pharmacology, 2012)

Mechanosensing of Cells in Laminin-Fuctionalized Biomembrane-Mimicking Substrates - Lautscham, Lena; Lin, Corey Y.; Auernheimer, Vera; Minner, Daniel; Goldmann, Wolfgang; Naumann, Christoph A.; Fabry, Ben (Biophysical Journal, 2013)

Microconstriction Arrays for High-Throughput Quantitative Measurements of Cell Mechanical Properties - Lange, Janina; Steinwachs, Julian; Kolb, Thorsten; Lautscham, Lena; Harder, Irina; Whyte, Graeme; Fabry, Ben (Biophysical Journal, 2015)

Migration in Confined 3D Environments Is Determined by a Combination of Adhesiveness, Nuclear Volume, Contractility, and Cell Stiffness - Lautscham, Lena; Kaemmerer, Christoph; Lange, Janina; Kolb, Thorsten; Mark, Christoph; Schilling, Achim; Strissel, Pamela; Strick, Reiner; Gluth, Caroline Laura Maria; Rowat, Amy C.; Metzner, Claus; Fabry, Ben (Biophysical Journal, 2015)
In cancer metastasis and other physiological processes, cells migrate through the three-dimensional (3D) extracellular matrix of connective tissue and must overcome the steric hindrance posed by pores that are smaller than the cells. It is currently assumed that low cell stiffness promotes cell migration through confined spaces, but other factors such as adhesion and traction forces may be equally important. To study 3D migration under confinement in a stiff (1.77 MPa) environment, we use soft lithography to fabricate polydimethylsiloxane (PDMS) devices consisting of linear channel segments with 20 ?m length, 3.7 ?m height, and a decreasing width from 11.2 to 1.7 ?m. To study 3D migration in a soft (550 Pa) environment, we use self-assembled collagen networks with an average pore size of 3 ?m. We then measure the ability of four different cancer cell lines to migrate through these 3D matrices, and correlate the results with cell physical properties including contractility, adhesiveness, cell stiffness, and nuclear volume. Furthermore, we alter cell adhesion by coating the channel walls with different amounts of adhesion proteins, and we increase cell stiffness by overexpression of the nuclear envelope protein lamin A. Although all cell lines are able to migrate through the smallest 1.7 ?m channels, we find significant differences in the migration velocity. Cell migration is impeded in cell lines with larger nuclei, lower adhesiveness, and to a lesser degree also in cells with lower contractility and higher stiffness. Our data show that the ability to overcome the steric hindrance of the matrix cannot be attributed to a single cell property but instead arises from a combination of adhesiveness, nuclear volume, contractility, and cell stiffness.
EVALuna2:17547

N-cadherin-functionalized polymer-tethered multi-bilayer: a cell surface-mimicking substrate to probe cellular mechanosensitivity - Ge, Y.; Lin, N. H.; Lautscham, Lena; Goldmann, Wolfgang; Fabry, Ben; Naumann, Christoph A. (Soft Matter, 2016)

Superstatistical analysis and modelling of heterogeneous random walks - Metzner, Claus; Mark, Christoph; Steinwachs, Julian; Lautscham, Lena; Stadler, Franz; Fabry, Ben (Nature Communications, 2015)

Superstatistical analysis and modelling of heterogeneous random walks - Metzner, Claus; Mark, Christoph; Steinwachs, Julian; Lautscham, Lena; Stadler, Franz; Fabry, Ben (Nature Communications, 2015)

The IsoStretcher: An isotropic cell stretch device to study mechanical biosensor pathways in living cells. - Schürmann, Sebastian; Wagner, Sören; Herlitze, Simon; Fischer, C.; Gumbrecht, S.; Wirth-Hücking, Anette; Prölß, Gerhard; Lautscham, Lena; Fabry, Ben; Goldmann, Wolfgang; Nikolova-Krstevski, V.; Martinac, B.; et al. (Biosensors and Bioelectronics, 2016)
Mechanosensation in many organs (e.g. lungs, heart, gut) is mediated by biosensors (like mechanosensitive ion channels), which convert mechanical stimuli into electrical and/or biochemical signals. To study those pathways, technical devices are needed that apply strain profiles to cells, and ideally allow simultaneous live-cell microscopy analysis. Strain profiles in organs can be complex and multiaxial, e.g. in hollow organs. Most devices in mechanobiology apply longitudinal uniaxial stretch to adhered cells using elastomeric membranes to study mechanical biosensors. Recent approaches in biomedical engineering have employed intelligent systems to apply biaxial or multiaxial stretch to cells. Here, we present an isotropic cell stretch system (IsoStretcher) that overcomes some previous limitations. Our system uses a rotational swivel mechanism that translates into a radial displacement of hooks attached to small circular silicone membranes. Isotropicity and focus stability are demonstrated with fluorescent beads, and transmission efficiency of elastomer membrane stretch to cellular area change in HeLa/HEK cells. Applying our system to lamin-A overexpressing fibrosarcoma cells, we found a markedly reduced stretch of cell area, indicative of a stiffer cytoskeleton. We also investigated stretch-activated Ca(2+) entry into atrial HL-1 myocytes. 10% isotropic stretch induced robust oscillating increases in intracellular Fluo-4 Ca(2+) fluorescence. Store-operated Ca(2+) entry was not detected in these cells. The Isostretcher provides a useful versatile tool for mechanobiolog

Vinculin phosphorylation at residues Y100 and Y1065 is required for cellular force transmission. - Auernheimer, Vera; Lautscham, Lena; Leidenberger, Maria; Friedrich, Oliver; Kappes, Bärbel; Fabry, Ben; Goldmann, Wolfgang (Journal of cell science, 2015)
The focal adhesion protein vinculin connects the actin cytoskeleton via talin and integrin with the extracellular matrix. Vinculin consists of a globular head and tail domain, which undergo conformational changes from a closed auto-inhibited conformation in the cytoplasm to an open conformation in focal adhesions. Src-phosphorylation has been suggested to regulate this conformational switch. To explore the role of phosphorylation in vinculin activation, we used knock-out mouse embryonic fibroblasts re-expressing different vinculin mutants in traction microscopy, magnetic tweezer microrheology, FRAP, and actin-binding assays. Compared to cells expressing wildtype or constitutively active vinculin, we found reduced tractions, cytoskeletal stiffness, adhesion strength, and increased vinculin dynamics in cells expressing constitutively inactive vinculin or vinculin where Src-phosphorylation was blocked by replacing tyrosine at position 100 and/or 1065 with non-phosphorylatable phenylalanine. Replacing tyrosines with phospho-mimicking glutamic acid restored cellular tractions, stiffness, adhesion strength as well as vinculin dynamics, and facilitated vinculin-actin binding. These data demonstrate that Src-phosphorylation is necessary for vinculin activation, and that phosphorylation controls cytoskeletal mechanics by regulating force transmission between the actin cytoskeleton and focal adhesion proteins.